2007
DOI: 10.1021/om070125d
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acidic Behavior of Fluorinated Organomercurials

Abstract: Owing to their unusual Lewis acidic properties, the coordination chemistry of fluorinated organomercurials is attracting increasing interest. In this review, the authors focus on the synthesis, structures, and properties of neutral Lewis adducts involving fluorinated organomercurials such as (CF 3 ) 2 Hg, (C 6 F 5 )HgCl, (C 6 F 5 ) 2 Hg, and [(o-C 6 F 4 )Hg] 3 . While most of these organomercurials form adducts with common Lewis basic organic substrates, [(o-C 6 F 4 )Hg] 3 also interacts with aromatic hydrocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
118
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(128 citation statements)
references
References 105 publications
10
118
0
Order By: Relevance
“…The crystal structure of 3 (Figure 1 a), which displays a virtually unchanged Hg À Sb separation of 3.073(1) , shows that the iodide anion is coordinated to the mercury center. [13] As nonfluorinated diarylmercury complexes do not form isolable adducts with any halides, [12,15] the coordination of the iodide ligand to the mercury atom of 3 constitutes a distinctive and noteworthy feature. The resulting mercury-iodine distance of 2.991(1) in 3 is also shorter than that observed in complexes involving highly Lewis acidic fluorinated organomercurials, such as [(C 6 F 5 ) 2 HgI] À (3.118 (2) ).…”
mentioning
confidence: 99%
“…The crystal structure of 3 (Figure 1 a), which displays a virtually unchanged Hg À Sb separation of 3.073(1) , shows that the iodide anion is coordinated to the mercury center. [13] As nonfluorinated diarylmercury complexes do not form isolable adducts with any halides, [12,15] the coordination of the iodide ligand to the mercury atom of 3 constitutes a distinctive and noteworthy feature. The resulting mercury-iodine distance of 2.991(1) in 3 is also shorter than that observed in complexes involving highly Lewis acidic fluorinated organomercurials, such as [(C 6 F 5 ) 2 HgI] À (3.118 (2) ).…”
mentioning
confidence: 99%
“…Besides, close disposition of mercury atoms promotes polydentate linkage with nucleophilic centres of a guest molecule. Thus, the macrocycle 1 was found to be able to interact with both anions [9][10][11][12][13] and neutral electron-rich molecules (see reviews [4,8,14] and recent studies cited in Refs. [15][16][17][18][19][20][21][22][23][24]).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24]). Coordination ability of 1 was utilized for molecular recognition in catalysis and organic synthesis [25][26][27], as well as for various ion-sensitive material chemistry, supramolecular self-assembly and design of crystalline materials [8,14]. Particularly, it was observed that macrocycle 1 is prone to form co-crystals with aromatic molecules and polyynes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that compound 1 shows promise in organic synthesis and catalysis, 1,2,11,12 for the molecular recognition, 13 as a ionophore for ion selective electrodes, 14 and for the design of new luminescent ma terials. 5 Earlier, 15 we have studied the reaction of macrocycle 1 with the borohydride anion in THF by IR (4), in which the anionic species is bound to the mercury centers of the anticrown by B-H-Hg bridges. According to quantum chemical calculations, 15 compounds 2, 3, and 4 should have pyramidal (half sandwich), bipyramidal, and sandwich structures, respectively (Fig.…”
mentioning
confidence: 99%